A wilder kingdom - Minteer, Ben A., 1969-; Greene, Harry W., 1945- (New York : Columbia University Press, 2023)
"Zoos have always had a vexed relationship to what is considered to be the "real" wild. Although zoos have come a long way over the past few decades in terms of aesthetics and ecological design, the sense that zoos can only ever offer poor facsimiles of the wild has persisted. Even in the largest, most immersive and naturlalistic zoos, animals are under pervasive and intense human control: diet, veterinary care, reproduction, and so on are all carefully managed and choreographed, with natural phenomena like disease minimized and death kept mostly hidden from public view. Some zoos are beginning to experiment more seriously with enhancing the wildness of their animals and exhibits, with implications for both zoo animals and visitor experience, as well as for the human relationship with wildlife and wild places beyond zoo gates. These concerns range across theory and practice, from the changing scientific and philosophical understandings of the wild and the compatibility of these often disparate ideas with the traditional zoo model, to the cultural, aesthetic, and psychological dimensions of this "wilder kingdom," to the practical demands of managing animals in more naturalistic and immersive exhibits effectively and safely. A Wilder Kingdom brings together a diverse and premier set of voices to ruminate on the elements and prospects of a wilder zoo"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Zoos -- Management; Zoo animals -- Environmental enrichment; Zoo animals -- Moral and ethical aspects; Jardins zoologiques -- Gestion; Animaux de jardin zoologique -- Enrichissement environnemental; Animaux de jardin zoologique -- Aspect moral; NATURE / Environmental Conservation & Protection; Zoos -- Management